Some Robust Tests for the Correlation Coefficient: A Comparative Study - Al-Noor, N. H.; Rasheed, H. A.; Sultan, A. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This paper is Interested with studying the performance of statistic test the hypothesis of independence of the two variables (the hypothesis that there is no correlation between the variables under study) in the case of data to meet the requirement of normal distribution in the case away from the distribution due to the presence of outliers (contaminated values) and compared with the performance of some of the other methods proposed and modified